2014
DOI: 10.1155/2014/843036
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Efficacy of Reflexology in Managing Patients with Diabetic Neuropathy: A Randomized Controlled Clinical Trial

Abstract: Background. The restricted usage of existing pharmacological methods which do not seem to provide the treatment of diabetic neuropathy may lead to exploring the efficacy of a complementary therapy. In this context, this paper was devoted to evaluate the efficacy of foot reflexology. This health science works on the hypothesis that the dysfunctional states of body parts could be identified by observing certain skin features and be rectified by stimulating certain specific areas mapped on feet. Method. Subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 25 publications
1
30
0
5
Order By: Relevance
“…The therapies evaluated by the remaining 16 trials were: Ponalrestat ICI 128436 , active analgesic controlled‐release oxycodone , vitamins and minerals , gabapentin enacarbil , neurotropic peptide ORG 2766 , Lipo‐PGE1 , QR‐333 topical cream , isosorbide dinitrate spray , clonidine gel , EMLA ® cream , reflexology and conventional therapy , photon stimulation 870 nm , magnetized foot insoles , transcutaneous electrical stimulation , unilateral surgical decompression , and Thai foot massage .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The therapies evaluated by the remaining 16 trials were: Ponalrestat ICI 128436 , active analgesic controlled‐release oxycodone , vitamins and minerals , gabapentin enacarbil , neurotropic peptide ORG 2766 , Lipo‐PGE1 , QR‐333 topical cream , isosorbide dinitrate spray , clonidine gel , EMLA ® cream , reflexology and conventional therapy , photon stimulation 870 nm , magnetized foot insoles , transcutaneous electrical stimulation , unilateral surgical decompression , and Thai foot massage .…”
Section: Resultsmentioning
confidence: 99%
“…All included studies met our inclusion criteria and all were RCTs. For 22 of the 27 included studies, the quality scores showed a low risk of bias (high quality) [2][3][4][5][6][7][8][9][10][11][12][13][14][17][18][19][20][21][22][23][24][25]. Some articles provided limited information on the design of the study, which led to unclear risk of bias scores.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations